2007
DOI: 10.1007/s10529-007-9417-3
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli malate dehydrogenase, a novel solubility enhancer for heterologous proteins synthesized in Escherichia coli

Abstract: Using 2-dimensional gel electrophoresis, the Escherichia coli proteome response to a heat-shock stress was analyzed and a 1.6-fold increase of malate dehydrogenase was observed even under the heat-shock condition where the total number of soluble proteins decreased by about 5%. We subsequently demonstrated that, as an N-terminus fusion expression partner, malate dehydrogenase facilitated the folding of, and dramatically increased the solubility of, many aggregation-prone heterologous proteins in E. coli cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Particularly, the expression of genes associated with two consecutive steps of the TCA cycle responsible for the conversion of malate to oxaloacetate by malate dehydrogenase (encoded by mdh and mqo ) and then to citrate by citrate synthase ( gltA ) kept increasing up to approximately 1.4-fold. This agreed with a previous E. coli proteome analyses of the HSR, which revealed that malate dehydrogenase was highly expressed under heatshock conditions, with the solubility of the recombinant proteins being dramatically increased when expressed with malate dehydrogenase as a fusion expression partner 32 . Another E. coli proteome analysis observed the high expression of citrate synthase under heat stress 16 .…”
Section: Resultssupporting
confidence: 92%
“…Particularly, the expression of genes associated with two consecutive steps of the TCA cycle responsible for the conversion of malate to oxaloacetate by malate dehydrogenase (encoded by mdh and mqo ) and then to citrate by citrate synthase ( gltA ) kept increasing up to approximately 1.4-fold. This agreed with a previous E. coli proteome analyses of the HSR, which revealed that malate dehydrogenase was highly expressed under heatshock conditions, with the solubility of the recombinant proteins being dramatically increased when expressed with malate dehydrogenase as a fusion expression partner 32 . Another E. coli proteome analysis observed the high expression of citrate synthase under heat stress 16 .…”
Section: Resultssupporting
confidence: 92%
“…These tags are not universally effective at promoting solubility and proper protein folding. Many novel solubility tags have been recently discovered by systematic investigations using proteomic studies, which were mainly carried out by Lee and his colleagues 92–96. These tags involve proteins that were significantly increased in the 2‐D gels from bacterial cells by exogenous stressors, such as guanidine hydrochloride (GdnHCl) or heat shock.…”
Section: Proteomic Approaches For Target‐specific Engineering In Bimentioning
confidence: 99%
“…These tags involve proteins that were significantly increased in the 2‐D gels from bacterial cells by exogenous stressors, such as guanidine hydrochloride (GdnHCl) or heat shock. The solubility tags identified in this set of analyses include Mdh (malate dehydrogenase) 96, PotD (spermidine/putrescine‐binding periplasmic protein), and Crr (glucose‐specific phosphotransferase (PTS) enzyme IIA component) 92, RpoS (RNA polymerase sigma factor) 95, SlyD (FKBP‐type peptidyl‐prolyl cis‐trans isomerase; PPIases) 93, and Tsf (elongation factor Ts) 94. These tags were highly effective as strong solubility enhancers in an E. coli cytosolic expression system for aggregation‐prone heterologous proteins, including human minipro‐insulin (mp‐INS), human epidermal growth factor (EGF), human interleukin‐2 (hIL‐2), human granulocyte colony‐stimulating factor (G‐CSF), and Pseudomonas putida cutinase (CUT).…”
Section: Proteomic Approaches For Target‐specific Engineering In Bimentioning
confidence: 99%